Substrate, moisture, temperature and seed germination of the threatened endemic tree Eriotheca vargasii (Malvaceae) - Mamani Mamani, Godofredo (2018)
We studied the germination of Eriotheca vargasii (Malvaceae), a poorly known endemic Peruvian Andean tree species characteristic of the dry forests of the Torobamba river valley, Peru. We determined seed characteristics, embryo morphology, viability, and assessed the influence of substrate (natural soil and commercially prepared media), temperature (controlled at 25 ºC and at ambient temperature between 18-22 ºC), and moisture (25 % and 50 % field capacity) on seed germination. Most seeds were ovoid in shape and although they contained well-developed embryos, only 46 % of them were viable. Substrate moisture levels had no influence on germination capacity or rate. In contrast, temperature and substrate type showed strong effects on germination. We observed the highest proportion of germinated seeds in prepared media at both temperatures tested (> 61 %). Furthermore, substrate types also influenced germination rates, with lower values in natural soil. The strongest effect on germination rates was by temperature, enhancing the difference in responses in substrate types (up to 90 % in commercially prepared media at 25 ºC). The low proportion of germinated seeds in soil (< 39 %), together with external local stress factors (e.g. grazing impact by herbivores), may be the critical factors contributing to the nearly total absence of seedlings and saplings of E. vargasii in the study area despite abundant seed production. In order to ensure a supply of E. vargasii seedlings for reforestation efforts, we recommend producing E. vargasii plants in nurseries and conducting reforestation trials. We suggest that germination of seedlings is done following guidelines from this study.